A Review Paper: Home Automation - Hemant T. Mahajan; Eashan Ganiga; Shweta Kalambe; Neha Bondre4; Gargi Dhabarde (Journal of Power Electronics and Devices, 2022)
The main objective of this project is to develop a home automation system using an AtMega 2560 board with GSM Module being remotely controlled by any Android OS smart phone. As technology is advancing so houses are also getting smarter. Modern houses are gradually shifting from conventional switches to centralized control system, involving remote controlled switches. Presently, conventional wall switches located in different parts of the house makes it difficult for the user to go near them. In this project we have made a similar and more convenient working model where the light, fans and PIR sensors can be controlled via smart phone also the change in temperature and humidity can be monitored on our smart phones and can be controlled by taking the required measures without taking much overhead. The project revolves around creating a home automation system prototype being the ability to lock/unlock a door through internet.